Global ammonia (NH3) retrieval from the FY-3F satellite hyperspectral infrared atmospheric sounder and performance assessment - Zhili Deng; Yapeng Wang; Minqiang Zhou; Ling Gao; Lin Chen; Xifeng Cao; Lingfeng Zhang; Yuhan Jiang; Haiyang Dou; Xingying Zhang (Atmospheric Environment, 2026)

Simple and large-scale preparation of HPAMAM/PVA sponge with robust mechanical properties for hexavalent chromium adsorption - Ji Gao; Li Cai; Lingfeng Zhang; Cunwei Fan; Hao Zhang; Jie Sun; Kai Guo (Journal of Environmental Chemical Engineering, 2026)

Ultra-stable and pH-universal photoelectrochemical photodetector achieved by CdSeTe/ZnS core-shell quantum dots - Jian Zhang; Yule Zhang; Songrui We; Han Zhang; Lingfeng Gao; Hao Wang; Chunxian Guo (Chemical Engineering Journal, 2025)

Discharge and deposition metallogenic model of “Datangpo-type” manganese deposits in China: Geophysical evidence from deep electrical structure of manganese-bearing grabens - Bingnan Yang; Xiangyun Hu; Lingfeng Gao; Xiaoqing Shen; Weiyang Liao; Jiajun Wang; Liangjun Yuan (Journal of Asian Earth Sciences, 2025)

Safety and Probiotics Evaluation of Bifidobacterial Genomes Isolated from Probiotic Products - Jue Li; Yinhuan Wang; Xingyu Xu; Xiaoling Zheng; Zhengnan Wang; Xiaofeng Chen; Lei Wang; Lingfeng Mao; Wangqin Ge; Huijun Liu; Wenwen Gao; Tingzhang Wang; et al. (Current Microbiology, 2025)

Adaptation of Marine Heterotrophic Protists to Long‐Term Warming Selection - Mengwen Pang; Zuyuan Gao; Lingfeng Huang; Chuk Man Chan; Xiaodong Zhang; Ruilin Su; Ke Pan; Hongbin Liu (Global Change Biology, 2025)
The rise in surface ocean temperature imposes strong effects on marine organisms. With large population sizes and fast generation times, microorganisms may rapidly adapt to ocean warming. However, long‐term experimental adaptation studies on heterotrophic protists are very limited, hindering our comprehensive understanding of their adaptation capability and the underlying mechanisms. In this study, we conducted long‐term thermal selection experiments on six representative marine protozoa. By assessing their phenotypes, metabolism, thermal performance curves, thermal traits, and carbon allocation status, we found that all investigated heterotrophic protists exhibited a fitness‐improved adaptation response to warming scenarios. After growing in warmer conditions for hundreds of generations (~850 for Cafeteria burkhardae and ~500 for other species), their optimal temperature and maximum rates of both growth and ingestion increased, whereas respiration rates significantly decreased. In addition, the cell size, cellular carbon, and nitrogen content at an elevated environmental temperature also increased after warming adaptation. Mechanisms underlying the increased competitive fitness at high temperatures after warming adaptation might be associated with the alleviated oxidative stress, shown by the remarkable reduction in cellular reactive oxygen species contents. Our study, for the first time, reveals the ability of marine heterotrophic protists to adapt to higher temperatures, providing experimental support for predictive modeling studies that integrate evolutionary potential with short‐term physiological responses, with important implications for marine ecosystem functioning and biogeochemical cycling under global warming.

Machine learning-based prediction of terrestrial heat-flow across mainland China - Chang Ni; Shan Xu; Xiangyun Hu; Xianchun Tang; Wenglong Zhou; Lingfeng Gao (Tectonophysics, 2025)

Microplastics magnify inhibitive effects of perfluorooctanoic acid on the marine microbial loop - Peichun Lin; Xiaokun Liu; Zuyuan Gao; Yelinzi Yuan; Hongbin Liu; Lingfeng Huang; Zhili He; Qinglu Zeng; Shanquan Wang (Environmental Research, 2025)

Oral pH-Sensitive Solid Self-Microemulsion of Norcantharidin Wrapped in Colon-Coated Capsule for Selective Therapy of Colorectal Carcinoma - Xia Liu; Wenyou Fang; Wenjie Lu; Mingchao Xu; Zijun Wu; Dan Su; Lingzhen Ding; Qing Zhang; Jinguang Ouyang; Tianming Wang; Lingfeng Sun; Song Gao; et al. (AAPS PharmSciTech, 2025)

Double network hydrogel confined MXene/Liquid metal by dynamic hydrogen bond for high-performance wearable sensors - Yuanwan Lou; Jingkun Wang; Yubo Peng; Xiaona Wang; Jianan Zhang; Lingfeng Chen; Wenchao Gao; Zhipeng Gao; Xiaona Li; Weiyi Chen; Min Zhao (Chemical Engineering Journal, 2024)

FSP1-mediated ferroptosis in cancer: from mechanisms to therapeutic applications - Ran Gao; Jinge Wang; Jingjing Huang; Tong Wang; Lingfeng Guo; Wenlu Liu; Jialu Guan; Desen Liang; Qinghui Meng; Huayang Pan (Apoptosis, 2024)

Impact of dielectric barrier discharge cold plasma on anthocyanin metabolism in blueberries: A targeted metabonomic and transcriptomic analysis - Lingfeng Xu; Zhenbo Gao; Ling Li; Jian Guo (Postharvest Biology and Technology, 2024)

Recent advances on environmental behavior of Cu-based nanomaterials in soil-plant system: A review - Jieyu Gao; Yi Zhu; Lingfeng Zeng; Xin Liu; Yuan Yang; Yaoyu Zhou (Journal of Environmental Management, 2024)

Cation-driven self-assembly of core–shell covalent organic frameworks@Ti3CN MXene nanospheres for high-performance aqueous zinc-ion hybrid supercapacitors - Kaige Zhang; Quan Zong; Kuixing Ding; Ying Wang; Lingfeng Gao; Dongdong Xu; Zhonghui Chen; Huanan Yu (Chemical Engineering Journal, 2024)

Wide-bandgap donor polymers from organic photovoltaics as dopant-free hole transport layers for perovskite solar cells - Hongtao Lai; Xin Yang; Liujiang Zhang; Leyu Bi; Binqiang Tian; Huanhuan Wang; Xingyu Gao; Lingfeng Lu; Bin Kan; Xiaofei Ji; Qiang Fu (Chemical Engineering Journal, 2024)

EEG-FRM: a neural network based familiar and unfamiliar face EEG recognition method - Chao Chen; Lingfeng Fan; Ying Gao; Shuang Qiu; Wei Wei; Huiguang He (Cognitive Neurodynamics, 2024)

Halide-chalcogenide hetero-structure for efficient and stable perovskite solar cells - Riming Nie; Zeliang Wei; Aarti Mehta; Lingfeng Chao; Jiaxing Gao; Weicun Chu; Zhongping Li; Han Miao; Yonghua Chen; Wanlin Guo (Chemical Engineering Journal, 2023)

Correction: Mucus-Penetrating Alginate-Chitosan Nanoparticles Loaded with Berberine Hydrochloride for Oral Delivery to the Inflammation Site of Ulcerative Colitis - Lingfeng Sun; Xiangjiang Nie; Wenjie Lu; Qing Zhang; Wenyou Fang; Song Gao; Shengqi Chen; Rongfeng Hu (AAPS PharmSciTech, 2022)

Mucus-Penetrating Alginate-Chitosan Nanoparticles Loaded with Berberine Hydrochloride for Oral Delivery to the Inflammation Site of Ulcerative Colitis - Lingfeng Sun; Xiangjiang Nie; Wenjie Lu; Qing Zhang; Wenyou Fang; Song Gao; Shengqi Chen; Rongfeng Hu (AAPS PharmSciTech, 2022)

Application of nanomaterials decorated with cyclodextrins as sensing elements for environment analysis - Lingfeng Gao; Chiyang He (Environmental Science and Pollution Research, 2021)

Three-Dimensional Fluid–Solid Coupling Numerical Simulation of Effects of Underlying Karst Cave on Shield Tunnel Through Sand Stratum - Wei Wang; Shiming Gao; Youwei Min; Lingfeng Liu; Jianping Chen (Geotechnical and Geological Engineering, 2019)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Spatial patterns and environmental correlates of bryophyte richness: sampling effort matters - Shengbin Chen; J. W. Ferry Slik; Lingfeng Mao; Jian Zhang; Rula Sa; Kexin Zhou; Jixi Gao (Biodiversity and Conservation, 2015)

Environmental determinants of geographic butterfly richness pattern in eastern China - Shengbin Chen; Lingfeng Mao; Jinlong Zhang; Kexin Zhou; Jixi Gao (Biodiversity and Conservation, 2014)

Microbial community of aerobic granules for ammonium and sulphide removal in a sequencing batch reactor - Caili Su; Lingfeng Zhu; Chuan Zhang; Xianghui Qi; Yiping Guo; Ruqin Gao (Biotechnology Letters, 2012)

Effect of starvation on biochemical composition and gametogenesis in the Pacific oyster Crassostrea gigas - Wenguang Liu; Qi Li; Fengxiang Gao; Lingfeng Kong (Fisheries Science, 2010)